A NOVEL METHOD FOR FRESH-CUT DECONTAMINATION: EFFICIENCY OF VAPORIZED ETHYL PYRUVATE IN REDUCING STAPHYLOCOCCUS AUREUS AND ESCHERICHIA COLI O157: H7 FROM FRESH PARSLEY - Tornuk, Fatih; Durak, Muhammed Zeki (WILEY, 2015)
Vaporized ethyl pyruvate (EP) was evaluated for its efficiency for decontamination of parsley from Escherichia coli O157: H7 and Staphylococcus aureus. Inoculated parsleys (similar to 10(4) or similar to 10(6) cfu/g) were treated with 0 (control sample), 100, 400 and 1,000 mu L of vaporized EP in 2.6-L closed-lid food containers. Samples were evaluated for bacterial growth and visual acceptance during treatment. In the case of decontamination of E. coli O157: H7, 1,000 mu L EP treatments completely inhibited the bacterial population and enabled 100% growth inhibition levels (GILs) in both inoculum levels. In low inoculation of S. aureus, the difference between the counts of the control and 1,000 mu EP-treated samples was higher than 2 logs after the storage. In high inoculum, 400 or 1,000 mu L EP-treated parsleys had significantly (P < 0.05) lower S. aureus populations as compared with the control sample. EP treatment retarded parsley decay; however, it caused some yellowness on the parsley leaves.
Keywords: ALLYL ISOTHIOCYANATE; SALMONELLA-TYPHIMURIUM; SPINACH LEAVES; WASH WATER; INACTIVATION; EFFICACY; QUALITY; PRODUCE; CINNAMALDEHYDE; DISINFECTANTS; Food Science & Technology